2014
DOI: 10.9790/2402-08318798
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties of Tiger nut-Soy Milk Extract

Abstract: Fresh tigernut and soybean seeds were processed and blended at different proportions to formulatesix new products of natural Tigernut-Soy Milk Extract (TSME) samples: (TME: SME)-100: 0=A, 90:10=B, 80:20=C, 70:30=D, 60:40=E and 50:50=F

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The mineral content of kunun aya in this study revealed high level of calcium, this relative high content of calcium in kunun aya indicates that it will promote strong teeth and bone development in children and adults. Potassium is an essential nutrient with important role in the synthesis of amino acids and proteins [29] the potassium content obtained in this study is in accordance with the report of [9] who reported that kunun-aya has an appreciable level of potassium. A low sodium content has recorded in this which makes kunun-aya a good beverage for diabetic and hypertensive patient [12] Iron is an important element that supplies the red blood with haemoglobin and prevents anaemia and other related diseases in pregnant women, nursing mothers, infants and elderly people [30], this study revealed an appreciable level of iron which is in accordance with the report of [27].Despite the nutritious value of kunnu aya as revealed in this research, the presence of feacal colifoms is of public health concern because teaming populace especially students rely on this drinks as cheap alternative to the bottled soft drinks.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mineral content of kunun aya in this study revealed high level of calcium, this relative high content of calcium in kunun aya indicates that it will promote strong teeth and bone development in children and adults. Potassium is an essential nutrient with important role in the synthesis of amino acids and proteins [29] the potassium content obtained in this study is in accordance with the report of [9] who reported that kunun-aya has an appreciable level of potassium. A low sodium content has recorded in this which makes kunun-aya a good beverage for diabetic and hypertensive patient [12] Iron is an important element that supplies the red blood with haemoglobin and prevents anaemia and other related diseases in pregnant women, nursing mothers, infants and elderly people [30], this study revealed an appreciable level of iron which is in accordance with the report of [27].Despite the nutritious value of kunnu aya as revealed in this research, the presence of feacal colifoms is of public health concern because teaming populace especially students rely on this drinks as cheap alternative to the bottled soft drinks.…”
Section: Discussionsupporting
confidence: 91%
“…All the samples were found to be acidic {3.9 -4.6}. This level of acidity of kunun aya has been recorded by several researchers including [2], [27]and [9] who attributed this to the presence of certain species of lactic acid bacteria namely Lactobacillus leichmani and Lactobacillus fermentum during the fermentation process, the acidic nature of this beverage may also be due to the fact that kunun aya might have started undergoing spoilage even before the time of purchase and such may lead to certain metabolites and could bring about reduction in pH of the product [2] According to [2] the low pH of kunun aya is not supposed to permit the growth of pathogenic microorganisms, but the presence of Escherichia coli, Staphylococcus aureus, Klebsiella spp., Proteus spp. and Salmonella spp.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…El-Bialy et al (2020) speculate that this may be due to the high carbohydrate content of milk made from corn and milk made from potato flour. Adedokun et al (2014) stated that a mixture of milk beverage manufactured from bambaranut, tigernut, and coconut contained 81.04-81.22% moisture, in contrast to Awonorin and Udeozor's (2014) observed that the moisture levels of tigernut-soy milk extract ranged between 81.71 and 86.41%. The use of different extraction methods and blending ratios for mixed milk beverages may be the root of the variation in moisture content (Adedokun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tiger nut, sorghum, and bean soaked water were taken out. Water was combined with tiger nuts, sorghum, and beans in the following ratios: 1:6, 1:7, and 1:5 (w/v) (Sanni et al, 1999;Awonorin and Udeozor, 2014). The mixture was then blended, with the tiger nuts and sorghum being heated to 80°C for 10 minutes and the bean for 30 minutes.…”
Section: Methods Preparation Of Alternative Milkmentioning
confidence: 99%